METODOLOGI PENELITIAN AL-TIBB AL-NABAWI PERSPEKTIF PENELITIAN ILMIAH - bin Salman, Abdul Matin (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2016)
This present paper is heavily influenced by this notion of inter-connectivity, trying specifically to demonstrate the correlation between the Prophet traditions on medication and modern health sciences. The Prophet medication project aims not at discovering utterly new ideas, but it reinforces any truth and denies false claims accredited to the Prophet. This paper, thus, focuses on both examining the medication practiced by the Prophet and exercising the accuracy of its sources. The basic argument developed in this paper is that transcendental objectivity within the Prophet traditions and empirical rationality within medical sciences must correlate. Through this examination, this paper concludes that the medication practiced by the Prophet as described in his traditions can be used as complementary to the modern medical treatment. Moreover, as long as it is carried out by using objective and accurate scientific methods, the Prophet medication can be used as an alternative to heal some diseases which modern medication has not found their cures. Keywords: Prophet traditions, prophet medication, scientific methods.